Homegreens: Aquaponics and Education - Carreira, Rute (2021)
The Homegreens project aims to develop small freshwater or saltwater aquaponic systems, which can be in-stalled in schools, serving as a pedagogical tool for the apprenticeship of subjects such as biology and sustaina-bility to the juvenile audience. A multidisciplinary team of designers, biologists, and agronomists was responsi-ble for the project’s research. The development and installation of experimental models, for qualitative analy-sis of user interaction, determined the methodology layout. This small-scale aquaponic system consists of two different grow beds, an aquarium with a capacity of 45L, a separating barrier for plants’ roots, a biofilter mesh with an integrated aerator, a valve for sediment cleaning, and two tripods. The involvement and the interaction with the Homegreens’ aquaponic system provides a group learning oppor-tunity, which contributes to environmental literacy in children with relevant values and experiences.